Rectosigmoid Localization of Radiopaque Markers Does Not Correlate with Prolonged Balloon Expulsion in Chronic Constipation: Results from a Multicenter Cohort. (July 2015) - Staller, Kyle; Barshop, Kenneth; Ananthakrishnan, Ashwin N; Kuo, Braden
Abstract : OBJECTIVES: Ingestion of radiopaque markers (ROMs) is a common means of assessing colonic transit time in chronic constipation. Because anorectal manometry (ARM) testing for pelvic floor dysfunction is mostly limited to academic centers, clinicians frequently use rectosigmoid accumulation of markers as a surrogate for pelvic floor dysfunction. We sought to determine whether rectosigmoid localization of markers on a ROM study correlated with measures of pelvic floor dysfunction by ARM and balloon expulsion testing. METHODS: We assembled a multicenter, retrospective cohort of patients diagnosed with chronic constipation who underwent both transit testing by ROM transit testing and ARM with balloon expulsion testing. We compared the proportion of patients with outlet obstruction by rectoanal pressure gradient or prolonged balloon expulsion stratified by marker location. RESULTS: There were 610 patients with both ROM testing and ARM with balloon expulsion testing. The mean age was 44 years and 526 were women (86%). Eighty‐one (13%) patients had markers confined to the rectosigmoid area alone and were compared with 529 patients with markers elsewhere (51%) or no retained markers (49%). Of those with markers confined to the rectosigmoid colon, 48 (59%) had a prolonged balloon expulsion compared with 276 (52%) who did not have rectosigmoid markers ( P =0.28). The mean rectoanal gradient for patients with markers in the rectosigmoid colon was −29±46 mm Hg compared with −34±59 mm Hg for all others ( P =0.59). CONCLUSIONS: Among patients with chronic constipation undergoing ROM transit testing, there is no association between rectosigmoid location of markers and rectoanal gradient or prolonged balloon expulsion.